Through-the-thickness selective laser ablation of ceramic coatings on soda-lime glass. (1st May 2017) - Romoli, L.; Khan, M.M.A.; Valentini, M.
Abstract: This paper investigates through-thickness laser ablation characteristics of ceramic coating deposited on the bottom surface of the soda-lime glass substrate. Experimental studies were focused on determining the effects of energy density, hatch distance and coating color on the ablation completion index. Effect of glass thickness was also tested to verify the robustness of the designed process. Up to a certain threshold limit, the ablation completion index is energy-limited and has an inverse U-shape relationship with the energy density input. Since greater hatch distance means faster ablation and lesser ablation completion index, there must be a tradeoff between ablation completion index and hatch distance. During through-thickness laser ablation of ceramic coating, energy density input should be in the range of 0.049 J/mm 2 – 0.251 J/mm 2 for black ceramic coating and 0.112 J/mm 2 – 0.251 J/mm 2 for other coatings. Finally, the designed process is capable of ablating the ceramic coating effectively through varied thickness. Highlights: Through-the-thickness laser ablation characteristics of ceramic coating was investigated. Effect of glass thickness was also tested to verify the process robustness. Up to a certain threshold limit, ablation completion index is energy-limited. There must be a tradeoff between ablation completion index and hatch distance. Designed process is able to ablate the ceramic coating through varied thickness.